Penghayatan Nilai-nilai Pendidikan Karakter Pada Pembelajaran Kitab Akhlaq Lil Banin Dalam Pembentukan Karakter Santri Pondok Pesantren Al Qur'an Al Furqon Cimulang Bogor - Wahida Putri (Universitas Pahlawan Tuanku Tambusai, 2022)
Education today is still oriented only on learning by theory, so the question of character and morality of students is one indication of students' lack of religious value, especially from moral aspect. Boarding schools are an alternative that needs to be exemplified in applying value education in character creation to learners, as boarding schools are known as character education. The study is to answer questions in a set of problems that include: (1) how is the study of the akhlaq lil banin in the messaging hut of the qur 'an al furqon cimbe (2) how the concept of applying character education in the akhlaq lil banin (3) how the concept of applying character education to the study of the akhlaq lil banin in the formation of the sanstri character in the monastery of the qur 'an al furqon cimre. The study USES a cumulative approach. The point of qualitative research is that data collected is not Numbers, but data that comes from text interviews, field notes, personal documents, memo logs, and other official documents. The results of this study may be known that the practice of study of akhlaq lil banin's book is full of character values and can shape character in santri, as seen by the attitude and conduct of santri tauladan later on out of the hut. Keywords: Character Education, The Book Of Akhlaq Lil Banin, Students Character